J-Shaped relationship between the red cell distribution width to albumin ratio and erectile dysfunction: a cross-sectional study from NHANES 2001-2004 - Xu, Yang; Li, Shuofeng (Frontiers in Endocrinology, 2025)
BackgroundErectile dysfunction (ED) is a prevalent condition closely associated with systemic inflammation and metabolic disorders. The red cell distribution width to albumin ratio (RAR) is an emerging inflammatory marker; however, its relationship with ED remains poorly understood.MethodsThis study conducted a cross-sectional analysis of data from 3,950 participants in the National Health and Nutrition Examination Survey (NHANES) 2001–2004 cycle to evaluate the association between RAR and ED risk. A Multivariable logistic regression model was employed to assess the relationship between RAR and ED, while a generalized additive model (GAM) and dose-response analysis were utilized to explore potential nonlinear associations. Subgroup analyses were performed to investigate interactions with demographic and lifestyle factors.ResultsAmong the study population, 1,157 individuals reported a history of ED. The prevalence of ED was significantly higher in individuals aged 50 years and older (86.78%) and was associated with increased rates of hypertension, diabetes mellitus, and cardiovascular disease (P < 0.001). A J-shaped relationship was identified between RAR and ED risk. Specifically, the risk of ED significantly increased below the RAR threshold of 3.42 (OR = 3.01, 95% CI: 2.08–4.36, P < 0.001), while the risk plateaued at higher RAR values. Subgroup analyses revealed significant interactions with ethnicity (P = 0.018) and moderate-intensity physical activity (P = 0.004). Non-Hispanic whites (OR = 2.85) and individuals engaging in moderate-intensity activity (OR = 3.83) exhibited a heightened risk of ED. No significant interactions were observed for other variables, including age and BMI.ConclusionThe results demonstrated that RAR was independently associated with ED risk, exhibiting a J-shaped relationship. There was a significant increase in risk below RAR = 3.42, with saturation occurring after exceeding this threshold.